TINJAUAN PUSTAKA : SEJARAH HIV (HUMAN IMMUNODEFICIENCY VIRUS) HINGGA PERKEMBANGAN VAKSINASI GLOBAL - wil hel minah (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2022)
ABSTRACT HIV (Human Immunodeficiency Virus) is a virus that damages the immune system by infecting CD4 cells (cluster of differentiation 4) which is an important part of the immune system. Damage to the immune system causes humans to lose their immune system so they are easily infected and die [1] . In March 2021, HIV cases were still increasing, as many as 427,201 people with HIV cases, and as many as 131,417 people with AIDS cases. The number of patients taking antiretroviral treatment was 269,289 people, 219,898 people were still alive and 49,391 people had died [2]. Until now there is no vaccine that can be used for HIV treatment, this trial has not succeeded in developing a working vaccine [3] . The purpose of this review is to explain the history of the development of HIV to the development of vaccines as technological updates for HIV treatment. The main challenges faced by this trial were the high antigenic variation of HIV, the presence of a latent HIV reservoir, and the difficulty of eliciting a broad neutralizing antibody response [4]. Currently, the strategy of making vaccines using traditional methods, namely Live attenuated virus, inactivated virus is not recommended for HIV treatment. Researchers have explored a new approach, namely mRNA vaccines. With this vaccine strategy it has been proven safe and effective to elicit CTLs (Cytotoxic T Lymphocytes) responses. Currently the HIV mRNA vaccine candidate from the company Moderna on August 18, 2021 has entered a phase 1 clinical trial in humans finding that 97% of people who received the vaccination had an appropriate immunological response. Keywords : Human Immunodeficiency Virus, Acquired immunodeficiency syndrome, Antiretroviral, HIV Vaccine, Self-amplifying.